Northernmost record of the Metatheria: a new Late Cretaceous pediomyid from the North Slope of Alaska. (2nd November 2019) - Eberle, Jaelyn J.; Clemens, William A.; McCarthy, Paul J.; Fiorillo, Anthony R.; Erickson, Gregory M.; Druckenmiller, Patrick S.
Abstract : The northernmost record of Metatheria, Unnuakomys hutchisoni gen. et sp. nov., is described from the Pediomys Point locality in Upper Cretaceous (lower Maastrichtian) strata of the Prince Creek Formation cropping out along the Colville River on the North Slope of Alaska, USA (70°N). Based on over 60 specimens (including tooth-bearing dentaries and a maxillary fragment), the new taxon is unusual in having two well-developed stylar cusps in the C position flanking the deepest part of the ectoflexus. To examine the relationship between U. hutchisoni and other metatherians, U. hutchisoni was scored into the taxon character matrix of other studies. Our results corroborate prior studies that suggest the new Alaskan pediomyid. However, in contrast to other studies, we do not recover a sister-group relationship between U. hutchisoni and Pediomys elegans . Rather, our study suggests that U. hutchisoni is more closely allied with Aquilan species Iqualadelphis lactea and ? Aquiladelphis laurae . Teeth of U. hutchisoni greatly outnumber those recovered from other mammals at Pediomys Point, like Late Cretaceous localities in the Western Interior where metatherians are among the most abundant mammalian fossils. However, what differs between Late Cretaceous mid-latitude localities and the assemblage from the North Slope of Alaska is metatherian richness. Whereas other studies have reported up to a dozen species of metatherians from Late Cretaceous mid-latitude North American assemblages, to date all the metatherian teeth collected from Pediomys Point appear to belong to just U. hutchisoni . A sampling bias may play a role in this pattern. This can be tested through additional collection from the Prince Creek Formation. However, the abundance of U. hutchisoni at Pediomys Point implies that this tiny metatherian thrived in an environment well above the Arctic Circle whose climatic extremes may have acted as a biogeographical filter to other metatherians. As the first mammal to be described from the Prince Creek Formation, U. hutchisoni provides support for the existence of a northern high-latitude early Maastrichtian faunal province identified by others on the basis of its distinctive dinosaurian fauna – the Paaŋaqtat Province. http://zoobank.org/urn:lsid:zoobank.org:pub:0EF38E01-2FF4-4698-A3AD-97CF2EE6847A